Universality from nuestra América: Open Issues to Rethink Human Rights - López López, Francisco Octavio (2024)
This work is a philosophical dissertation in which the concept of universality is problematized with the aim of connecting it to the political realm of human rights. Currently, both the concept of universality and the notion of human rights are deeply discredited, necessitating an urgent reformulation to liberate them from the abstract connotation usually associated with them. Three aspects of universality are explored: the human condition as a universal reality, universality in identity plurality, and political universality. Ultimately, a practical tripartite modelis introduced to reconsider the concept of human rights, enabling the articulation of demands from diversesocial groups and mobilizing them into political action.